Is peer support a tipping point for the opioid use disorder crisis in Appalachia? Research holds the answer - Kimberly Horn; Stephanie M. Mathis; Lara Nagle; Angela Hagaman; Mary Beth Dunkenberger; Robert Pack (BMC, 2024)
Abstract Background The present commentary highlights the pressing need for systematic research to assess the implementation and effectiveness of medications for opioid use disorder, used in conjunction with peer recovery support services, to improve treatment outcomes for individuals with opioid use disorder in Central Appalachia. This region, encompassing West Virginia, Eastern Kentucky, Southwest Virginia, East Tennessee, and Western North Carolina, has long grappled with a disproportionate burden of the opioid crisis. Due to a complex interplay of cultural, socioeconomic, medical, and geographic factors, individuals in Central Appalachia face challenges in maintaining treatment and recovery efforts, leading to lower success rates. Approach To address the issue, we apply an exploratory approach, looking at the intersection of unique regional factors with the utilization of medications for opioid use disorder, in conjunction with peer recovery support services. This combined treatment strategy shows promise in addressing crucial needs in opioid use disorder treatment and enhancing the recovery journey. However, there are significant evidence gaps that need to be addressed to validate the expected value of incorporating peer support into this treatment strategy. Conclusion We identify nine obstacles and offer recommendations to address the gaps and advance peer recovery support services research. These recommendations include the establishment of specific partnerships and infrastructure for community-engaged, peer recovery support research; improved allocation of funding and resources to implement evidence-based practices such as peer support and medication-assisted treatment; developing a more precise definition of peer roles and their integration across the treatment and recovery spectrum; and proactive efforts to combat stigma through outreach and education.